The CARMENES Survey: A Search for Terrestrial Planets in the Habitable Zones of M Dwarfs. Issue Volume 8:Issue S293(2012) (29th April 2014) - Quirrenbach, A.; Amado, P. J.; Caballero, J. A.; Mandel, H.; Mundt, R.; Reiners, A.; Ribas, I.; Carrasco, M. A. Sánchez; Seifert, W.; Azzaro, M.; Galadí, D.; ,
Abstract: CARMENES (C alarA lto high-R esolution search forM dwarfs withE xo-earths withN ear-infrared and opticalE chelleS pectrographs) is a next-generation instrument under construction for the 3.5 m telescope at the Calar Alto Observatory by a consortium of eleven Spanish and German institutions. The scientific goal of the project is a five-year exoplanet survey targeting 300 M stars with the completed instrument. The CARMENES hardware consists of two separate échelle spectrographs covering the wavelength range from 0.55 to 1.7 μm at a spectral resolution of R = 82, 000, fed by fibers from the Cassegrain focus of the telescope. Both spectrographs are housed in a temperature-stabilized environment in vacuum tanks, to enable a long-term radial velocity precision of 1 m s −1 employing a simultaneous calibration with Th-Ne and U-Ne emission line lamps.